AB0002 The Relation of Rorc Gene Polymorphisms on Severity of Rhemumatoid Arthritis. (9th June 2015) - Paradowska-Gorycka, A.; Pawlik, A.; Raszkiewicz, B.; Malinowski, D.; Romanowska-Prochnicka, K.; Haladyj, E.; Manczak, M.; Olesinska, M.
Abstract : Background: Rheumatoid arthritis is one of the chronic autoimmune diseases, with genetic and environmental predisposition. Th17 cells constitute the third effector arm of Th cells, complementing the Th1 and Th2 lineages. RORc expressing Th17 cells produce cytokines, including IL-17, IL-6, IL-21, IL-22 and TNF-α, with pro-inflammatory effects, which appear to have a role in immunopathogenesis of RA. The orphan nuclear receptor - RORc2 is the master transcription factor that can drive Th17 cell differentiation in humans, which make it one of the key factors that may affect the course of the RA. Objectives: Assessment of the correlations between polymorphisms (rs9826 A/G, rs12045886 T/C and rs9017 G/A) in RORc2 gene, and severity of RA. Evaluation of RORc2 protein expression in serum samples from RA patients and healthy controls. Methods: All the SNPs in the RORc2 gene were detected using PCR-RFLP method and TaqMan SNP genotyping assay. Serum levels of RORc2 protein in study groups were measured by enzyme-linked immunosorbent assay (ELISA). Results: Evaluation of RORc2 protein expression in serum samples from RA patients showed that its level is significantly increased compared to samples from healthy controls (p=0, 013). Also significant correlation between RORc2 rs9826 A allele and clinical parameters was observed in RA patients. rs9826 AA and AG genotypes have been linked with higher mean values of CRP (p=0, 001), creatinine (p=0.024) and VAS (p=0, 014). Moreover we manage to established that dominant model (AA + GA) of rs9017 RORc2 gene polymorphism is associated with higher mean value of CRP and VAS (p=0, 0005 and p=0, 006 respectively). We also observed that carriers of rs9017 A allele had a tendency to have a higher DAS 28-CRP (p=0, 057) and HAQ score (p=0, 075) Conclusions: Our results for the first time showed the relationship between RORc2 gene polymorphisms and and severity of RA. RORc2 rs9826 A/G variant may be considered as genetic risk factors for RA severity. RORc2 protein levels may be associated with the pathogenesis of RA in the Polish population References: Yang L, Anderson DE, Baecher-Allan C et al. IL-21 and TGF-beta are required for differentiation of human T(H)17 cells. Nature. 2008;454(7202):350-2. Leipe J, Grunke M, Dechant C et al. Role of Th17 cells in human autoimmune arthritis. Arthritis Rheum. 2010;62(10):2876-85. Ganjalikhani Hakemi M, Ghaedi K, Homayouni V et al. Positive and Negative Regulation of Th17 Cells Differentiation: Evaluating The Impact of RORC2. Cell J. 2013; 16(3). Acknowledgements: Funding: This work was supported by a grant from the Polish National Science Center (2011/01/D/NZ5/01396). Disclosure of Interest: A. Paradowska-Gorycka Grant/research support from: Polish National Science Center (2011/01/D/NZ5/01396)., A. Pawlik: None declared, B. Raszkiewicz: None declared, D. Malinowski: None declared, K. Romanowska-Prochnicka: None declared, E. Haladyj: None declared, M. Manczak: None declared, M. Olesinska: None declared